2018
DOI: 10.36574/jpp.v2i3.51
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Voluntary Disclosure in Indonesia State-Owned Enterprises Annual Reports

Abstract: The purpose of this research is to investigate the determinants of voluntary disclosure in the annual reports of Indonesia State Owned Enterprise ("SOE"). A content analysis was applied to 60 SOEs' annual reports to assess the extent of SOEs voluntary disclosure, and Ordinary Least Squares ("OLS") regression was conducted to examine the relationship between explanatory variables and the extent of SOEs voluntary disclosure. The results show that SOEs disclose more about nonfinancial than strategic and financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Several previous studies have shown that companies voluntarily make many disclosures. Fadila (2018) stated that the increase in voluntary disclosure is in line with the size of the company, and that there are three reasons for large-scale companies to disclose information: (1) the disclosure has a relatively low cost, (2) the disclosure of information facilitates market access and financing, and (3) the disclosure does not jeopardise the company's position. In addition to company scale, other factors affect the voluntary disclosure of information.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have shown that companies voluntarily make many disclosures. Fadila (2018) stated that the increase in voluntary disclosure is in line with the size of the company, and that there are three reasons for large-scale companies to disclose information: (1) the disclosure has a relatively low cost, (2) the disclosure of information facilitates market access and financing, and (3) the disclosure does not jeopardise the company's position. In addition to company scale, other factors affect the voluntary disclosure of information.…”
Section: Introductionmentioning
confidence: 99%